PRINCIPLES OF PRESENTING MORPHOLOGICAL CATEGORIES IN RIZOUDDIN IBN FAKHRIDDIN’S WORK KITOB AT-TASRIF (World Bulletin of Education and Learning, 2025)
This article analyzes the principles of presenting morphological categories in Rizouddin ibn Faxriddin’s Kitob at-Tasrif and their scientific foundation. The study examines the formation rules of verbs, nouns, and functional categories, their connection with syntactic and semantic context, and compares medieval Arabic linguistic traditions with modern approaches. The research methods include historical-typological, comparative, and philological analysis. The results indicate that Rizouddin ibn Faxriddin’s approach is based on systematic classification and functional methodology, making it a significant scientific source for the study of Arabic morphology.
Keywords: Rizouddin ibn Faxriddin, morphological categories, verb and noun, arabic linguistics, systematic classification, functional approach.